Bauhaus Weimar : Entwürfe für die Zukunft. - Bothe, Rolf; Günther, Gitta; Herrmann, Siegfried; Reissinger, Elisabeth; Reuter, Brigitte; Siebenbrodt, Michael; Vogelsang, Bernd; Wahl, Volker; Winkler, Klaus-Jürgen (Ostfildern-Ruit : Hatje Cantz Verlag, 2000)
Ackermann, Suse ; Albers, Josef ; Arndt, Alfred ; Baschant, Rudolf ; Bayer, Herbert ; Berthold, Johannes ; Bogler, Friedrich Wilhelm ; Bogler, Theodor ; Brandt, Marianne ; Breuer, Marcel ; Brocksieper, Heinrich ; Citroen, Paul ; Determann, Walter ; Dicker, Friedl ; Dieckmann, Erich ; Driesch, Johannes ; Feininger, Julia ; Feininger, Lyonel ; Fischer, Georg ; Fricke, Hans ; Graeff, Werner ; Grewenig, Leo ; Grohs, Hans ; Gropius, Walter ; Häberer, Paul, ; Hantschk-Arndt, Gertrud ; Hartogh, Rudolf Franz ; Helm, Dörte ; Hilker, Reinhard ; Hirschfeld-Mack, Ludwig ; Hoffmann-Lederer, Mila ; Itten, Johannes ; Jahn, Martin ; Jucker, Carl Jakob ; Jungnik, Hedwig ; Kandinsky, Wassily ; Keler, Peter ; Klee, Paul ; Klemm, Walther ; Koch-Otten, Benita ; Krehan, Max ; Langenstrass-Ulig, Magda ; Lindig, Otto ; Lutz, Rudolf ; Maltan, Josef ; Marcks, Gerhard ; Meyer, Adolf ; Mögelin, Else ; Moholy-Nagy, Laszlo ; Molnár, Farkas ; Muche, Georg ; Müller-Hummel, Theobald Emil ; Pap, Gyula ; Peiffer-Watenphul, Max ; Rittweger, Otto ; Roghé, Agnes ; Röhl, Karl Peter ; Scheper, Hinnerk ; Scheper-Berkenkamp, Lou ; Schlemmer, Oskar ; Schmidt, Joost ; Schmidt, Kurt ; Schrammen, Eberhard ; Schreyer, Lothar ; Schwertfeger, Kurt ; Siedhoff-Buscher, Alma ; Singer, Franz ; Slutzky, Naum ; Steinkühler, Theodor ; Stölzl, Gunta ; Teltscher, Georg ; Téry-Adler, Margit ; Thalmann, Max ; Wagenfeld, Wilhelm ; Wassiljew, Nikolai ; Weber, Vincent ; Weininger, Andor ; Willets, Margarete
Duits
boek
Keywords: Weimar